Small-subunit rRNA genes and in situ hybridization with oligonucleotides specific for the bacterial symbionts in the larvae of the bryozoan Bugula neritina and proposal of "Candidatus endobugula sertula". - Haygood, M G (1997)
Larvae of the bryozoan Bugula neritina harbor bacterial symbionts. These symbionts were identified as a novel species of gamma-proteobacterium, based on ribosomal small-subunit rRNA gene sequences. In situ hybridization with oligonucleotides specific for the symbiont confirmed the origin of the sequence. The taxonomic status "Candidatus Endobugula sertula" is proposed for the larval symbiont.